1980
DOI: 10.1002/bit.260220102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pore diffusion limitation on dextrin hydrolysis by immobilized glucoamylase

Abstract: Data reported here and previously indicate that when dextrin is hydrolyzed in the presence of immobilized glucoamylase, use of a larger average molecular weight substrate leads to lower overall rates of hydrolysis, while the maltose concentration during the bulk of the reaction and the maximum glucose concentration are lower than when the soluble form of the enzyme is employed under the same conditions. Computer simulation of the system demonstrated that all three observations were caused by pore diffusion lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This series of linked reactions can cause diffusion limitation of the product species from the pore spaces of the enzyme microspheres, and this phenomena could affect the overall rate of hydrolysis. Lee et al26 reported that when the glucose concentration were very high, a higher rate of reversion was observed with the products being isomaltose and nigorose.…”
Section: Resultsmentioning
confidence: 99%
“…This series of linked reactions can cause diffusion limitation of the product species from the pore spaces of the enzyme microspheres, and this phenomena could affect the overall rate of hydrolysis. Lee et al26 reported that when the glucose concentration were very high, a higher rate of reversion was observed with the products being isomaltose and nigorose.…”
Section: Resultsmentioning
confidence: 99%
“…4 that eqs. (16) and (17) indeed predict curved lines under certain conditions. There are several studies reported in the l i t e r a t~r e " ,~~-~,~.~,~~ which report linear So x vs In (1 -x) plots obtained experimentally.…”
Section: High Somentioning
confidence: 91%
“…The low cost of metals and the reuse of adsorbents for hundreds of times without any detectable loss of metal‐chelating properties are the attractive features of metal affinity separation 20. Immobilization of AMG has been studied using various supports, such as activated carbon,21 polymeric support,22 and inorganic materials 23. Drawback of the enzyme immobilization includes activity decrease and diffusion limitations of the substrate, the intermediate, and the product.…”
Section: Introductionmentioning
confidence: 99%